On soil districts - Alexandre M.J.-C. Wadoux; Léa Courteille; Dominique Arrouays; Lucas De Carvalho Gomes; Jérôme Cortet; Rachel E. Creamer; Einar Eberhardt; Mogens H. Greve; Erik Grüneberg; Roland Harhoff; Gerard B.M. Heuvelink; Ina Krahl; et al. (Geoderma, 2024)
In 2023, the European Commission released a legislative proposal for a Directive on Soil Monitoring and Resilience which aims to define a legal framework to achieve healthy soils across the European Union (EU) by 2050. A key component of the initial Directive is the mandate for Member States to establish basic geographic soil governance units, referred to as soil districts, and appoint a district-specific authority to oversee the implementation of soil health assessments. This paper proposes an operational definition of the districts following the conditions outlined in the proposal for the Directive and discusses various attention points for their implementation. Tentative districts were developed for seven EU countries, considering soil type, climate, topography, and land cover factors, starting from the smallest existing administrative unit (i.e. municipalities). Experts were asked to report on the applicability of the proposed districts within well-known pedo-ecological regions and discuss the relevance of the districts for establishing an EU-wide monitoring network and reporting on soil health and degradation. The outcomes highlight the need for detailed soil maps to account for specific soil types when stratifying countries into soil districts. The soilscape approach allows for a consistent method to defining soil districts across Member States. This enables contrasting soils within a district to be managed in a similar manner, with soil degradation/health thresholds applied to each district based on land cover. However, it is unclear whether soil districts as currently formulated in the Directive are in fact the right tool to support local soil management and monitoring of soil health. Districts can help ensure that all soil conditions are covered in a monitoring system, but they may not provide support for soil management or monitoring at a local scale due to short-scale soil variability and threats affecting soil management within the same soilscape. Beyond the use of districts for designing a European/national scale monitoring system, the districts can help create animations and other educational tools to promote soil literacy and connectivity of users to soils locally.